Routine pelvic X-rays in asymptomatic hemodynamically stable blunt trauma patients: A meta-analysis. Issue 11 (November 2018) - van Trigt, Jessica; Schep, Niels; Peters, Rolf; Goslings, Carel; Schepers, Tim; Halm, Jens
Abstract: Introduction: There is no consensus on how pelvic X-rays should be ordered selectively in blunt trauma patients which may save time, reduce radiation exposure and costs. The aim of this systematic review and meta-analysis was to assess the need for routine pelvic X-rays in awake, respiratory and hemodynamically (HD) stable blunt trauma patients without signs of pelvic fracture. Criteria to identify patients who could safely forgo pelvic X-ray were evaluated. Methods: A literature search was performed for prospective comparative cohort studies. Inclusion criteria were: blunt force trauma, hemodynamically and respiratory stable and awake patients, physical examination (PE) for pelvic fractures was adequately described, and the reliability of negative PE findings could be evaluated. Primary outcome was the negative predictive value (NPV) of PE for all and for clinically relevant pelvic fractures. Additionally sensitivity, specificity and positive predictive value (PPV) were calculated. Results: Ten studies were included; yielding a total of 11, 423 patients. The NPV of PE for all pelvic fractures ranged from 0.96 to 1.00 with a median of 0.996. Combining studies, total NPV was 0.991. For clinically relevant fractures, the NPV of PE ranged from 0.996 to 1.00 with a median of 1.00. In patients with negative findings during PE, 0.9% had fractures, and 0.1% had clinically relevant fractures, none requiring surgical management. Conclusions: In awake, hemodynamically and respiratory stable blunt trauma patients, PE could identify those patients who could safely forgo pelvic X-ray. Selective ordering of pelvic X-ray may lead to a decrease in patient work-up time, lower radiation exposure, and reduce costs. A decision making flow chart is proposed..